Development Of The Treasure Hunt: Fun Math Card Game Gamification-Based Learning Media To Enhance Critical Thinking Skills In Social Arithmetic - Soemantri, Sandha; Pramesti, Citra Aliffadya; Maisyaro, Maisyaro; Munawwaroh, Nur Mahmudah; Al Falah, Shofia; Alifia, Zalfa (Inteligensi : Jurnal Ilmu Pendidikan, 2024)
This study aims to develop and evaluate gamification-based learning media, Treasure Hunt: Fun Math Card Game, to improve students' critical thinking skills and understanding of social arithmetic at junior high school level. Specifically, this research aims to explore a more engaging and interactive approach to encourage students' motivation and critical thinking skills. This research used an RD approach with the ADDIE model. Data were collected through observation, pre-test and post-test, as well as feedback from students. Data were analysed using descriptive and inferential statistical methods to measure the improvement of students' engagement, motivation, and critical thinking skills. The results showed that the use of Treasure Hunt game significantly improved students' engagement, motivation, and understanding of social arithmetic. Students showed improved critical thinking skills in solving arithmetic problems, compared to traditional learning methods. These findings demonstrate the effectiveness of gamification in making abstract mathematical concepts more interesting and easy to understand.